The origin and evolution of cultures - Boyd, Robert, 1948- (Evolution and cognition., 2005)
Oxford presents, in one convenient and coherently organized volume, 20 influential but until now relatively inaccessible articles that form the backbone of Boyd and Richerson's path-breaking work on evolution and culture. Their interdisciplinary research is based on two notions. First, that culture is crucial for understanding human behavior; unlike other organisms, socially transmitted beliefs, attitudes, and values heavily influence our behavior. Secondly, culture is part of biology: the capacity to acquire and transmit culture is a derived component of human psychology, and the contents of culture are deeply intertwined with our biology. Culture then is a pool of information, stored in the brains of the population that gets transmitted from one brain to another by social learning processes. Therefore, culture can account for both our outstanding ecological success as well as the maladaptations that characterize much of human behavior. The interest in this collection will span anthropology, psychology, economics, philosophy, and political science.